(3GdaUhd GdEjdGbjI aj cdjGJ GdWHs - (3TQa GdOjf CHj YHO Gddg eMeO Hf jhSa GdEjdGbjs ((3MSf Hf jMji Hf MGeO s)
(3ChdgG (B:s
(3HYO GdHSedI(B: (3GdMeO ddg QH GdYGdejf , hGdYGbHI ddeJbjf Cbhd (B: (3Ef GdWH jYQa efg CMhGd HOf GdEfSGf ef LgI eG jUM, hjRhd Yf GdUMI , dJMaX GdUMI MGUdI , hJSJQO RGFdI s
(3BNQgG (B:s
(3hceG jDNP dhGLH ef GdaUO dVYa GdeYOI Ch GdESgGd eJbOe Gh ZKjGf aj GdMGd hGddg CYde hGMce HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3egedI GdfbWs
(3hocJHJ GdYfGhjf HGdMeQIs
(3haj JQGbje GdUaMGJ HYV GdEVWQGHs
(3ceeG LGAJ hQbJG (B19 s
20 (3ebdhHJjf YfO GdJLdjO s
(3bQf GdfSN (B:s
Keywords: (3GdWHs